Effects of dinuclear copper(II) complexes with 6-(benzylamino)purine derivatives on AhR and PXR dependent expression of cytochromes P450 CYP1A2 and CYP3A4 genes in primary cultures of human hepatocytes - Dvorák, Zdenek; Vrzal, Radim; Starha, Pavel; Klanicová, Alena; Trávnícek, Zdenek (Toxicology in vitro, 2010)
A series of dinuclear copper(II) complexes of the compositions [Cu(2)(micro-L(n))(2)(micro-Cl)(2)Cl(2)] (1, 2), [Cu(2)(micro-L(n))(4)Cl(2)]Cl(2).2H(2)O (3, 4) and [Cu(2)(micro-L(n))(4)(ClO(4))(2)](ClO(4))(2).xSolv (5, 6; xSolv=4MeOH for 5 and 2EtOH for 6), involving 6-(benzylamino)purine derivatives (L(n)), have been evaluated with the aim to determine their possible drug interactions and their capability to induce the expression of major drug-metabolizing cytochromes P450. The above-mentioned complexes have been chosen based on the fact that substantial both in vitro (cytotoxicity, SOD-mimic) and in vivo (antidiabetic) biological activity has been found for them. As models, primary cultures of human hepatocytes and human hepatoma cells HepG2 transiently transfected with a plasmid containing dioxin-responsive element fused to the luciferase reporter gene (DRE-LUC) have been chosen. It has been found that the tested complexes 1-6 did not significantly induce the expression of CYP1A2 and CYP3A4 mRNAs in the concentration range of 0.1-10.0microM, in three different primary human hepatocyte cultures after 24h of the treatment. On the other hand, the model inducers, i.e. 2,3,7,8- tetrachlorodibenzo-p-dioxin (TCDD) and rifampicin, significantly increased the levels of CYP1A2 and CYP3A4 mRNAs in all cultures. In addition, compounds 1-6 did not transactivate DRE-LUC in transiently transfected HepG2, while TCDD strongly induced luciferase activity after 24h of incubation. Based on the obtained results, it may be concluded that the studied dinuclear copper(II) complexes 1-6 possess very low toxicological potential to cause drug interactions in terms of transcriptional activation of the major human cytochromes P450.
Keywords: hepatocyty; dospělí; pregnanový X receptor; Cytochrome P-450 CYP3A; Gene Expression Regulation, Enzymologic; regulace genové exprese enzymů; Adult; puriny; Molecular Structure; lidé; receptory aromatických uhlovodíků; cytochrom P-450 CYP3A; messenger RNA; kultivované buňky; měď; Hepatocytes; Copper; RNA, Messenger; Humans; molekulární struktura; Cells, Cultured; Pregnane X Receptor; Receptors, Aryl Hydrocarbon; Cytochrome P-450 CYP1A2; Male; Receptors, Steroid; Aged; benzylové sloučeniny; Purines; lidé středního věku; senioři; cytochrom P-450 CYP1A2; mužské pohlaví; Middle Aged; Benzyl Compounds; steroidní receptory